Effects of Dietary Protein Levels on Fecal Amino Acids Excretion and Apparent Digestibility, and Fecal and Ileal Microbial Amino Acids Composition in Weaned Piglets - Yang, Zhenguo; Deng, Huan; He, Tianle; Sun, Zhihong; Gifty, Ziema Bumbie; Hu, Ping; Rao, Zebing; Tang, Zhiru (Frontiers in Nutrition, 2021)
Background and aims: The purpose of this study was to determine the effects of low protein diets with the same Lys, Met+Cys, Thr and Trp levels as high protein diets on the fecal amino acid excretion and apparent digestibility and ileal and fecal microbial amino acids composition in weaned piglets. Methods: Fifty-four 21-day-old Duroc × Landrace × Yorkshire weaned piglets were randomly divided into 3 groups and fed with corn-soybean meal basal diets, in which the CP content were 20% (H-CP), 17% (M-CP) and 14% (L-CP), respectively. The experiment included 7-day adaptation period and 45-day trial period. Six piglets in each group were randomly slaughtered on d 10, d 25 and d 45 of the trial period, and the intestinal contents, intestinal mucosa and feces were collected. Results: The results showed that the interaction between feeding time and dietary CP levels was reflected in the apparent digestibility of dietary CP and AA (P < 0.01). With the increase of age, the apparent digestibility of CP and AA were increased (P < 0.01). With the increase of CP levels, the excretion of nitrogen (N) were decreased (P < 0.01), while the flow of microbial AA in ileum and feces were increased (P < 0.01). The interaction between feeding time and dietary CP levels was also reflected in the composition of AA in ileum and stool of piglets (P < 0.01). The proportion of His, Lyr, Met, Cys and Ser was lower than the average, while the proportion of Phe, Leu, Pro, Ala, Glu and Asp was higher than the average. With the increase of age, the AA content of microorganisms increased (P < 0.01). Conclusion: All in all, this paper revealed the changes of N, CP and AA excretion and digestibility of feces and microorganisms of piglets under the combined action of different dietary protein levels and different feeding time, as well as the changes of AA composition of intestinal microorganisms and AA composition of microorganisms.